Intercompany Financing “Implementation of Arm’s Length Principle to the LG Shared Service Center Short-term Intercompany Financing” - Sherlyta Utomo (iBuss Management, 2018)
Due to the increasing activities of the tax authority and transfer pricing monitoring by the government and also international organizations, the rules of transfer pricing are keep on updated. As a result, multinational enterprises must comply with those regulations over time. OECD as an international organization launch a principle called Arm’s Length Principle, which states that an internal transaction must be carried as it is performed to the unrelated party. Thus, in this paper the author developed a model for the client to apply the principle through clear steps. There are 5 internal interiew participants which the author has chosen with a judgemental strategy. According to the study, the client should follow four big steps. The first step is to determine the type of service being performed. The second step is to determine the ALP method. The third step is to assign the borrowers’ credit rating. Then from the credit rating, the amount of intercompany loan margin can be made, which is the last step. By applying the model, the company can save from the tax adjustment and save a lot of time and efforts to achieve the optimum tax efficiency. Keyword:Arm’s Length Principle, Transfer Pricing, Intercompany Transaction, Corporate Income Tax, Short Term Loan